Peningkatan Pengetahuan Perilaku Hidup Bersih dan Sehat (PHBS) tentang Jajanan Sehat di MI PUI Cicanggong Kawali - Delia Agustina; Imel Puji Astuti; Siti Nur amanah; Sri Nurul Rohimah (Kolaborasi: Jurnal Pengabdian Masyarakat, 2023)
Introduction : Improving health status is strongly influenced by behavioral factors, namely proactive behavior that is useful for maintaining and improving health, preventing the risk of infection, protecting oneself from disease threats and actively participating in community empowerment activities called the Health Promotion Center, since 1996 known as the Behavioral Program. Clean and Healthy Living (PHBS). The health of school children is currently a priority scale, from the results of the 2013 population census it was found that a group of children in Indonesia totaled around 66 million people / 28% of the total population in Indonesia. Elementary school children are an age group that is vulnerable to nutrition and disease, especially infectious diseases. Objective : The purpose of this counseling is to improve the knowledge of grade 4 MI PUI Cicanggong students about healthy and nutritious snacks, as well as efforts to reduce the poor nutritional status of snacks. Method : The methodology of health education that incorporates self-management. Participants in this counseling are anticipated to be able to apply a complete strategy, particularly in the creation of new behaviors, specifically PHBS in the school setting as well as the community. Result : From the results it can be concluded that before carrying out health counseling as many as 6 people (22.2%), participants were able to answer questions before the material was delivered, 15 people did not know (71.0%) participants did not know about healthy snacks, 4 people (14.8 %) participants did not know participants did not know healthy snacks. then after carrying out health education, the knowledge of participants about healthy snacks PHBS increased to 25 people 100%. Conclusion : Increasing knowledge about healthy snacks is a good start to instill clean and healthy living habits in schools. So, after knowing the characteristics of unhealthy snack food and the dangers of unhealthy snack food, it is hoped that students will not buy unhealthy.